Given that i − 3 and β are both roots of P ( x ) = a x 3 + 9 x 2 + a x − 3 0 , where a and β are real numbers, find the value of a + β .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since P(x) as described is of all real coefficients,
x = -3 + − 1
⟹ ( x + 3 ) 2 = − 1
⟹ x 2 + 6 x + 1 0 = 0
Since α γ = 1 0 , {Here is the trap of this question for -10 by mistake of other way.}
a 3 0 = α β γ = 1 0 β .
Hence β = a 3 .
(x - a 3 )( x 2 + 6 x + 1 0 ) = 0
⟹ a x 3 + ( 6 a − 3 ) x 2 + ( 1 0 a − 1 8 ) x − 3 0 = 0
6 a - 3 = 9 ⟹ a = 2
Checked that 10 a - 18 = 10 (2) - 18 = 2 = a which is correct.
β = a 3 = 2 3
a + β = 2 + 2 3 = 2 7
Answer: 2 7
Problem Loading...
Note Loading...
Set Loading...
Since a is a real number, then P ( x ) is a real polynomial, and thus − i − 3 is another root of P ( x ) . Now, since ( x − ( i − 3 ) ) and ( x − ( − i − 3 ) ) are two linear factors of P ( x ) , we can write:
P ( x ) = a ( x − ( i − 3 ) ) ( x − ( − i − 3 ) ) ( x − β ) = a ( x 2 + 6 x + 1 0 ) ( x − β ) Where β is the real root.
Now, factorizing the main coefficient in the original expression, we have: P ( x ) = a ( x 3 + a 9 x 2 + x − a 3 0 )
From equating both expressions for P ( x ) , we get:
a ( x 3 + a 9 x 2 + x − a 3 0 ) = a ( x 3 + ( 6 − β ) x 2 + ( 1 0 − 6 β ) x − 1 0 β ) Equating coefficients of x 2 and independent terms, we get:
− a 3 0 = − 1 0 β ⇒ a β = 3 a 9 = 6 − β ⇒ a β = 6 a − 9
Solving simultaneously for a and β , we get a = 2 and β = 2 3 . Hence:
a + β = 2 + 2 3 = 2 7